Detection of frailty in elderly cancer patients: Improvement of the G8 screening test. Issue 2 (March 2016) - Petit-Monéger, Aurélie; Rainfray, Muriel; Soubeyran, Pierre; Bellera, Carine A.; Mathoulin-Pélissier, Simone
Abstract: Objective: The G8 is a screening test to identify frail elderly patients with cancer. Objectives were to design and evaluate the performance of alternative tests taking into account other predictive domains for frailty. Methods: We conducted a literature review to identify predictive factors of frailty. Using a Delphi consensus, we collected 24 European experts' opinions to validate the most relevant items to improve the G8. Alternative tests were created and performance assessed on a development population (ONCODAGE cohort). The highest performing test was compared to the G8, and validated through both an internal and an external population validation (Aquitaine Geriatric Oncology cohort). Results: The study population consisted of 1435 patients (ONCODAGE cohort) and 364 patients (Aquitaine Geriatric Oncology cohort). Twenty-three experts validated two items with a strong consensus (> 75%): modification of the threshold for the G8 polypharmacy item to six drugs per day and replacement of the G8 item on neuropsychological problems by four Instrumental Activities of Daily Living (IADL) items predictive of incident dementia, creating three modified G8 tests (addition of either item, or both). Only the G8 IADL-modified test had better performance than the G8 when tested on the ONCODAGE cohort: sensitivity = 77%, specificity = 67%. This test was validated on the internal (sensitivity = 78%, specificity = 71%) and external (sensitivity = 88%, specificity = 69%) validation populations. Conclusion: Adding the four IADL items improves the performance of the G8. We have developed and validated a G8-modified test that is more specific than the G8 to detect frail elderly, while still sensitive and feasible in less than 10 min.